Understanding the SO2 Degassing Budget of Mt Etna's Paroxysms: First Clues From the December 2015 Sequence - D'Aleo, Roberto; Bitetto, Marcello; Delle Donne, Dario; Coltelli, Mauro; Coppola, Diego; McCormick Kilbride, Brendan; Pecora, Emilio; Ripepe, Maurizio; Salem, Lois Claire; Tamburello, Giancarlo; Aiuppa, Alessandro (Frontiers in Earth Science, 2019)
The persistent open-vent activity of Mt. Etna volcano, in Sicily, is frequently punctuated by some of the most spectacular paroxysmal basaltic explosions in nature. Although magmatic gas is unquestionably the driver of these events, direct measurements of a paroxysm’s gas flux budget have remained challenging and limited in number, to date. A particularly violent paroxysmal sequence took place on Etna on December 2015, intermittently involving four of its summit craters, especially the Voragine (VOR) that had previously displayed no activity for several years. Here, we characterize the volcano’s SO2 degassing budget prior to, during and after this paroxysmal sequence, using ground-based (UV-Camera) and satellite (OMI) observations, complemented with thermal (thermal cameras and MODIS) measurements from both ground and space. We make use of the high spatial resolution of UV-cameras to resolve SO2 emissions from the erupting VOR crater for the first time, and to characterize temporal switches in degassing activity from VOR to the nearby New Southeast Crater (NSEC). Our data show that onset of paroxysmal activity on December 3-5 was marked by visible escalation in VOR SO2 fluxes (4700-8900 tons/day), in satellite-derived thermal emissions (2000 MW vs. ~2-11 MW July-November 2015 average), and in OMI-derived daily SO2 masses (5.4±0.7 to 10.0±1.3 kilotonnes, kt; 0.5 kt was the average in the pre-eruptive period). Switch in volcanic activity from VOR to NSEC on December 6 was detected by increasing SO2 fluxes at the NSEC crater (up to 3460±350 tons/day), and by decaying SO2 emissions at VOR, until activity termination on December 19. Taken together, our observations infer the total degassed SO2 mass for the entire VOR paroxysmal sequence at 21,000±2730 t, corresponding to complete degassing of ~1.9±0.3 Mm3 of magma, or significantly less than the measured erupted magma volumes (5.1-12 Mm3). From this mismatch, we propose that a sizeable fraction of the erupted magma during the paroxysms was stored and degassed in the volcano’s shallow plumbing system well before eruption.